DETERMINANTS OF LEARNERS' SATISFACTION IN OPEN DISTANCE LEARNING PROGRAMMES IN NIGERIA: Sunday Abidemi Itasanmi, Mathew Taiwo Oni (PJDOL, 2023)
This study focuses on examining the relationship, and contribution of teaching and learning experiences, educational resources, technical support service, and infrastructure to the determination of learners' satisfaction in Open Distance Learning programmes in Nigeria. The study is guided with four research questions, and a descriptive research design approach was adopted for the study. A sample size of 719 students was randomly selected from three (3) purposively selected ODL institutions in Southwestern Nigeria. A semi-structured questionnaire duly validated was used in collecting data for the study. Data collected were analysed using frequency counts, percentages, Pearson Product Moment Correlation, and regression analysis. Results revealed that there is a significant relationship between teaching and learning experience, educational resources, technical support and infrastructure, and general satisfaction of students in ODL programmes. Also, age, sex, and school significantly jointly predict the general satisfaction of students in ODL programmes among other results.